Facile approach to the fabrication of 3D cellulose nanofibrils (CNFs) reinforced poly(vinyl alcohol) hydrogel with ideal biocompatibility. (1st October 2017) - Chen, Xiao; Chen, Chuntao; Zhang, Heng; Huang, Yang; Yang, Jiazhi; Sun, Dongping
Highlights: CNFs reinforced Poly(vinyl alcohol) porous hydrogel were successfully fabricated and characterized. A significant improvement in the mechanical and thermal features was recorded. The hydrogen bonds and interpenetrating polymer network contributed to the higher water/PBS retention and absorption rate. Abstract: In this study, the reinforcing effects of cellulose nanofibrils (CNFs) on poly (vinyl alcohol) (PVA) matrix were explored. And ethylene glycol was used to enhance the water content and phosphate buffer saline (PBS) absorbency. The morphological aspects of the hydrogel were studied by transmission electron microscope (TEM) and scanning electron microscopy (SEM). The presence of interactions, changes in crystallinity as well as thermal behaviour were investigated by Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD) and thermogravimetry respectively. With the increase of CNFs concentration, the composite greatly improved its mechanical strength while maintaining remarkable ductility through tensile test results. The positive results of cell toxicity test suggested our porous hydrogel could provide ideal cell growth environment. This work revealed that CNFs hydrolysed by bacterial cellulose could perform as a perfect reinforcing agents which is of great interest in the fields of biotechnology and biomedicine with the potential values in cell culture, co-cultivation, as well as biomedical scaffold materials.